Konsep Etis Religius dengan Pendekatan Maqashid Syariah Perspektif Thaha Abd Al-Rahman - Edo Segara Gustanto; Asmuni Asmuni; Rusdi Rizki Lubis (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2024)
This study aims to understand and analyze the concept of religious ethics in the Maqasid al-Shariah approach according to Thaha Abd al-Rahman. The method used is a qualitative method with a philosophical approach and textual analysis. Data were collected through literature studies, interviews, and document analysis. The results of this research indicate that the thoughts of Thaha Abd Al-Rahman provide valuable contributions to the development of a contextual, ethical, and relevant Islamic paradigm for the current era. By integrating alternative modernity concepts, belief as a foundation, religious ethics, and maqasid shariah, Taha Abd Al-Rahman forms a solid foundation for the realization of a just, equitable, and ethical society in the modern era. The implication of this research is that the concept of religious ethics in the Maqasid al-Shariah approach by Taha Abd al-Rahman can be a guide for Muslims in their daily lives. It is recommended that educational institutions, both formal and informal, introduce this concept to the community to improve their understanding of religious ethics in Islam.